A novel cyclization/oxidation strategy for a two-step synthesis of (Z)-aurone. Issue 14 (5th April 2017) - Li, Siyuan; Jin, Feng; Viji, Mayavan; Jo, Hyeju; Sim, Jaeuk; Kim, Hak Sung; Lee, Heesoon; Jung, Jae-Kyung
Graphical abstract: Highlights: Two-step synthesis of ( Z )-Aurones through cyclization/oxidation cascade reaction. A novel AgNO3 -promoted synthesis of diversely substituted aurones was developed. ( Z )-Aurones were obtained in good yields with excellent regio- and diastereoselectivity. Abstract: An efficient and facile two-step strategy for the synthesis of ( Z )-aurone from arylacetylenes and salicyladehydes, via silver(I) nitrate mediated cyclization/oxidation in the presence of potassium carbonate has been developed. The key feature of our method was delicate cascade reaction, to provide the corresponding ( Z )-aurone in high yield and good regio- and stereo selectivity.